EKSPLORASI MAKNA "TEMAN BELAJAR" BAGI SISWA KELAS II SD DALAM MEMBANGUN SEMANGAT BELAJAR - Suhermi, Lulut; Restalia, Winda; Ani, Ani (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
Learning enthusiasm is a crucial factor in the academic achievement of elementary school students. In the second grade, social interactions with peers begin to play a significant role. This study focuses on understanding the meaning of "study buddy" from the students' own perspective and its contribution to building learning enthusiasm. It explores the meaning of "study buddy" and describes the role of study buddy in building learning enthusiasm according to second grade elementary school students. This study uses a qualitative approach with a phenomenological method. Data collection was conducted through passive participant observation and semi-structured in-depth interviews with 8 second grade elementary school students selected using a purposive sampling technique. Data were analyzed using the Miles and Huberman data analysis model (data reduction, data presentation, and conclusion drawing). The research findings reveal three main themes. First, study buddy is interpreted as a "partner in difficulty" who is there to help each other with assignments. Second, study buddy as a "source of encouragement" through behaviors such as inviting, waiting, and providing verbal motivation. Third, study buddy as a "playmate" who makes the learning process feel fun and not boring. For second-grade elementary school students, a "study buddy" is not just a nearby individual, but rather a figure who provides academic, emotional, and social support. The presence of a study buddy creates a safe, enjoyable, and supportive learning environment, which ultimately significantly builds and maintains their enthusiasm for learning. The implications of this research can be considered by teachers to further encourage and design collaborative learning activities. ABSTRAKSemangat belajar merupakan faktor krusial dalam pencapaian akademik siswa sekolah dasar. Di jenjang kelas II SD, interaksi sosial dengan teman sebaya mulai memegang peran penting. Penelitian ini berfokus untuk memahami makna "teman belajar" dari perspektif siswa itu sendiri dan kontribusinya dalam membangun semangat belajar. Mengeksplorasi makna "teman belajar" dan mendeskripsikan peran yang dijalankan teman belajar dalam membangun semangat belajar menurut siswa kelas II SD. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Pengumpulan data dilakukan melalui observasi partisipan pasif dan wawancara mendalam secara semi-terstruktur terhadap 8 siswa kelas II SD yang dipilih dengan teknik purposive sampling. Data dianalisis menggunakan teknik analisis data model Miles dan Huberman (reduksi data, penyajian data, dan penarikan kesimpulan). Temuan penelitian mengungkap tiga tema utama. Pertama, teman belajar dimaknai sebagai "partner dalam kesulitan" yang hadir untuk saling membantu mengerjakan tugas. Kedua, teman belajar sebagai "sumber semangat" melalui perilaku mengajak, menunggu, dan memberikan motivasi verbal. Ketiga, teman belajar sebagai "teman bermain" yang menjadikan proses belajar terasa menyenangkan dan tidak membosankan. Bagi siswa kelas II SD, "teman belajar" bukan hanya sekadar individu yang berada di dekatnya, melainkan sebuah figur yang memberikan dukungan akademik, emosional, dan sosial. Keberadaan teman belajar menciptakan lingkungan belajar yang aman, menyenangkan, dan saling mendukung, yang pada akhirnya secara signifikan membangun dan menjaga semangat belajar mereka. Implikasi dari penelitian ini dapat menjadi pertimbangan bagi guru untuk lebih mendorong dan merancang aktivitas pembelajaran kolaboratif.